A critical review of the effectiveness of environmental assessment and modification in the prevention of falls amongst community dwelling older people. (March 2016) - Pighills, Alison; Ballinger, Claire; Pickering, Ruth; Chari, Satyan
Introduction: The potential of environmental assessment and modification to reduce falls has recently received attention within the gerontology literature. Research investigating the clinical effectiveness of this intervention in falls prevention reports conflicting results. Discrepancies are due to variation in the risk profile of study participants and the health care background of the person providing the environmental intervention or the intensity of the intervention provided. Method: The purpose of this paper is to compare and contrast two systematic reviews, which include meta-analyses, of environmental interventions for falls prevention in community dwelling older people, using the critical appraisal skills programme tool for systematic reviews. Findings: Both reviews found that: environmental assessment and modification was effective in falls prevention; intervention was effective with high but not low risk participants; and that high intensity environmental assessment was effective, whereas low intensity intervention was not. Environmental interventions which were delivered by occupational therapists were deemed high intensity, probably because their underpinning theoretical frameworks focus on the impact of the environment on function. Conclusion: We discuss possible reasons why occupational therapist led environmental assessment and modification is clinically effective in falls prevention, for people at high risk of falls, whereas non occupational therapist led intervention is not.